"Luna rubens": eclissi lunare in Orazio, ode 2,11? - Meli, Simone ca. 20./21. Jh. (Wiener Studien, 2024)
This paper proposes an interpretation of the phrase neque uno luna rubens nitet / voltu in Hor. carm. 2,11,10f. and analyses other occurrences of red moons in Horace's works (Hor. sat. 1,8), in his models (Sapph. fr. 96 V.) and in the Augustan and early imperial literary production (Virgil, Propertius, Ovid, Seneca) to prove, with the support of ancient and modern sources, that the phenomenon briefly described in this poem is a total lunar eclipse, which the poet might have witnessed. If such hypothesis is true, this detail could help us date the ode 2,11 to the year 26 BC, when a total lunar eclipse happened on May 13th and was visible from Rome not too late in the night.